New criteria on global asymptotic synchronization of Duffing-type oscillator system - Yi, Xuejun; Ren, Ling; Zhang, Zhengqiu (Nonlinear Analysis: Modelling and Control, 2020)
In this paper, we are concerned with global asymptotic synchronization of Duffing-type oscillator system. Without using matrix measure theory, graph theory and LMI method, which are recently widely applied to investigating global exponential/asymptotic synchronization for dynamical systems and complex networks, four novel sufficient conditions on global asymptotic synchronization for above system are acquired on the basis of constant variation method, integral factor method and integral inequality skills.